The Development of Stolen USB Storage with Deduced Location Alert - Loy, Mei Ting; Nurul Azma Abdullah, (Applied Information Technology And Computer Science, 2021)
This USB storage device with location alert functionality secure tool is proposed to protect the data in the device from being disclosed by automatically lock access to the device after certain conditions. Besides that, it features a users sign-in module where entering a correct password is necessary to access to the data storage device. Moreover, owner can track the info and approximated geolocation of the device’s latest connected computer through email alerts if that computer is connected to internet. Object oriented methodology is used as the methodology to develop this tool and Simple Mail Transfer Protocol (SMTP) was applied to enable automatic email alerts. With this tool, users are able to password protect their USB devices and receive email alerts for the details and approximate location of the devices’ latest connected computer. Development of this tool contributes to the protection of USB data storage device by solving issues in which lost or stolen USB device can be easily access by anyone obtained it since it lack of user access control module. Besides that this tool is expected to assist data storage device owner to recover their missing device by sending notification about the device’s latest connected computer to the owner.